2011
DOI: 10.3746/jfn.2011.16.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Conditions and Substrate Specificity for Trehalose Production by Resting Cells of Arthrobacter crystallopoietes N-08

Abstract: Recently, we found that Arthrobacter crystallopoietes N-08 isolated from soil directly produces trehalose from maltose by a resting cell reaction. In this study, the optimal set of conditions and substrate specificity for the trehalose production using resting cells was investigated. Optimum temperature and pH of the resting cell reaction were 55 o C and pH 5.5, respectively, and the reaction was stable for two hours at 37~55 o C and for one hour at the wide pH ranges of 3~9. Various disaccharide substrates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Morphologically distinguishable colonies were transferred on fresh nutrient agar, and cultured at 30°C for 24 h. A total of 116 strains were discriminated separately, and stored as frozen stock cultures at −70°C in nutrient broth with 20% (v/v) glycerol until use. All bacterial strains were individually cultured in nutrient broth medium for 3 days, and we monitored the potential for production of novel oligosaccharide in their culture supernatant by thin layer chromatographic (TLC) analysis as described by Seo and Shin ( 13 ). Among these, 6 bacterial strains (SS-02, SS-21, SS-27, SS-46, SS-65, and SS-76) were selected on the first screening because novel spots that previously did not exist on the TLC plate were expressed in the culture supernatant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologically distinguishable colonies were transferred on fresh nutrient agar, and cultured at 30°C for 24 h. A total of 116 strains were discriminated separately, and stored as frozen stock cultures at −70°C in nutrient broth with 20% (v/v) glycerol until use. All bacterial strains were individually cultured in nutrient broth medium for 3 days, and we monitored the potential for production of novel oligosaccharide in their culture supernatant by thin layer chromatographic (TLC) analysis as described by Seo and Shin ( 13 ). Among these, 6 bacterial strains (SS-02, SS-21, SS-27, SS-46, SS-65, and SS-76) were selected on the first screening because novel spots that previously did not exist on the TLC plate were expressed in the culture supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that a gram-positive bacterium, Arthrobacter crystallopoietes N-08, which extracellularly produces a high level of non-reducing glucooligosaccharide, namely trehalose [α-D-glucopyranosyl-( 1 , 1 )-α-D-glucophyranoside], from maltose by a resting cell reaction ( 13 , 14 ). Based on the previous results, in the present study, we screened diverse bacterial strains from various fermented foods to find a new bacterial strain producing oligosaccharides from maltose containing medium, and identified the structural characteristics of the oligosaccharide produced from the specific bacterium.…”
Section: Introductionmentioning
confidence: 99%
“…According to the isolation method of bacterial strains reported by Bae et al [16] and Seo and Shin [17], diverse bacterial strains were isolated from various Korean fermented food samples, such as soybean paste, soy sauce, and heavily salted fermented shrimp, to find novel strain that could produces new oligosaccharide. Briefly, from those fermented foods, individual strains were purely separated by diluting fermented food samples with saline solution, plating and culturing the solution on nutrient agar, and finally transferring morphologically distinguishable colonies onto fresh nutrient agar.…”
Section: Isolation Of Bacterial Strains From Various Fermented Foodsmentioning
confidence: 99%
“…All bacterial strains were cultured individually in nutrient broth medium for 1 day, and their potential to produce novel oligosaccharides was determined by analyzing the culture supernatant by TLC (Kieselgel 60 plate, Merck, Darmstabt, Germany), as described by Seo and Shin [17]. Briefly, harvested and washed cells were suspended with 100 mM acetate buffer (pH 5.5) containing 1% cellobiose, and incubated at 30°C for 4 h. When the culture supernatant was spotted and developed with eluent (BtOH:pyridine:water, 6:4:1) on the TLC plate, 6 bacterial strains (viz., SS-02, SS-21, SS-27, SS-46, SS-65, and SS-76) were found to produce oligosaccharides.…”
Section: Cultivation Of Bacterial Strains For Estimation Of Oligosaccmentioning
confidence: 99%
See 1 more Smart Citation